(untitled) (Revista Latino-Americana de Enfermagem, 1998)
Ergonomics has been one of the most important strategies for reducing musculoskeletal injuries caused by working conditions. The present report discusses particular aspects of the working environment such as work space, working heights, as well as the limits of reach and of the equipment used, and attempts to relate these to the occupational activities in nursing.